The Effect of Kufner Interfacing on the Collar Outcome of Men's Suit on Size M Dummy - Savitri, Riska; Nelmira, Weni (Gorga : Jurnal Seni Rupa, 2024)
This research is motivated by the need to understand the impact of Kufner interfacing on the collar results of men's blazers on size M dummies. The purpose of this study is to describe the results of the blazer collar based on three main aspects: flatness, neatness, and balance, using Kufner interfacing. This study used an experimental method conducted from November to February 2024. Primary data were obtained from the assessments of 16 panelists, consisting of 4 lecturers and 12 trained students. The research instrument was a questionnaire, and the data were analyzed using descriptive analysis and the Friedman test to test the hypothesis. The results showed that the use of Kufner interfacing resulted in flatness of 80.47%, neatness of 91.67%, and balance of 88.28%, with all aspects rated in the “Very Good” category. The hypothesis test showed that Kufner interfacing significantly affected the flatness, neatness, and balance of the blazer collar, with a probability value smaller than the significance level (p < 0.05). This indicates that Kufner interfacing provides optimal results in the process of making men's blazer collars on size M dummies.